Profile of individuals with cardiomyopathy patients - Das, Anjan Kumar; Kabir, Md Shahedul; Rahman, Md Taifur; Haque, Mohammad Amdadul; Ali, Mirza Mohammad Idris; Rahman, Abu Foyez Md Motiur (Journal of Dhaka National Medical College & Hospital, 2023)
Objective: To find out the socio-demographic and clinical profile of patients with cardiomyopathy in a tertiary care teaching hospital in Bangladesh. Methods: A descriptive, cross sectional study was conducted from July 2022 to December 2022 among 50 patients attending at Cardiology Outpatient Department of the Cumilla Medical College Hospital after obtaining requisite consent from the patients. Data were collected through the inter- viewing of the patients. The collected data were entered into the computer and analyzed by using SPSS (version 20.1) to know the socio-demographic and clinical profile of patients with cardiomy- opathy in a tertiary care hospital. The study was approved by the institutional ethical committee. Results: In a pool of 50 cardiomyopathic patients, 26 (52%) patients belong to 61-70 years old. More than half of the respondents were male (n-31, 62%). Overall, 33 (66%) patients have ejection fraction (LVEF) >25% while 17 (34%) patients have ejection fraction (LVEF) <25%. Pedal edema was the most commonly associated findings (66%) with cardiomyopathy followed by hypertension (46%), diabetes mellitus (42%) and dyslipidaemia (38%) Conclusion: Present study concluded that most of the patients of cardiomyopathy were male and belonged to age 61-70 year age group. J. Dhaka National Med. Coll. Hos. 2023; 29 (01): 34-36